The initial education of teachers in Chile: ‘voices’ of the Chilean community of research in Mathematics Education - Pino-Fan, Luis R.; Guzmán-Retamal, Ismenia; Larraín, Macarena; Vargas-Díaz, Claudia (Uniciencia, 2018)
In this article, we present the viewpoints of 17 nationally and internationally recognized Chilean researchers for their contributions to the field of mathematics education, and specifically to the training of mathematics teachers. For such purpose, a survey that explored the opinions and reflections of experts about the characteristics of the current mathematics teachers training programs in Chile was conducted. As a result of this study, some recommendations were proposed; they could be considered for the improvement of teacher training programs, allowing opportunities for acquisition of suitable didactic-mathematical competences for the management of the learning.